The Effects of Innovation Climate and Leadership on Innovation Performance: A Case Study in Malaysian Public Sector - Norasyikin Shaikh Ibrahim; Ahmad Fadzli bin Ahmad Tajuddin (Journal of Social Transformation and Regional Development, 2020)
At present, there are currently strategic challenges facing the Malaysian government, including debt, deficit pressures, technology, innovation and globalization. Hence, Malaysian public service agencies recognize that they need to be resilient. In other words, they need to respond to peopleâ€™s demand (adaptation), provide efficient and effective services (competitiveness) and make themselves reputable (value). This study aims to answer this question:  What are the factors that predict innovation in Malaysian public sector? The results reveal that both innovative climate and participative leadership are associated with the implementation of innovation in public organizations. In conclusion, implications on management practices and research are further discussed.